2008
DOI: 10.5007/2175-7925.2008v21n4p21
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos fisiológicos da toxidez de ácidos orgânicos em sementes de aveia

Abstract: ResumoPara que o cultivo da aveia (Avena sativa L.) seja também alternativo economicamente viável em solos de várzea, faz-se necessário a utilização de cultivares tolerantes aos principais ácidos orgânicos produzidos pela decomposição da matéria orgânica gerada em cultivos com plantio direto. O objetivo deste trabalho foi determinar a faixa de concentração e as respostas fi siológicas para serem utilizadas na cultivar UPF 16 para tolerância a ácidos orgânicos. Foram estudados os efeitos de cinco concentrações … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…In different butyric acid concentrations, Hyola 571CL showed a reduction for RPgerm.14 at 8mM, while Hyola 433 increased (Table 4). In oat cultivars, a reduction in the germination with increase in the butyric acid doses was also reported (TUNES et al 2008). Similarly, the behavior observed in Hyola 433 was also reported in oat genotypes; however, regarding other organic acids, at different concentrations of lactic and malic organic acids, increased percentage of germination up to certain concentrations was verified.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In different butyric acid concentrations, Hyola 571CL showed a reduction for RPgerm.14 at 8mM, while Hyola 433 increased (Table 4). In oat cultivars, a reduction in the germination with increase in the butyric acid doses was also reported (TUNES et al 2008). Similarly, the behavior observed in Hyola 433 was also reported in oat genotypes; however, regarding other organic acids, at different concentrations of lactic and malic organic acids, increased percentage of germination up to certain concentrations was verified.…”
Section: Resultssupporting
confidence: 67%
“…Considering propionic acid doses, RPsl and RPrl were not different between the concentrations tested ( Table 6). The opposite was found in oats, in which the root length was the most negatively affected (TUNES et al 2008). The increase in the concentration of organic acids leads to reduced root length and dry matter (TUNES et al 2012).…”
Section: Resultsmentioning
confidence: 93%
“…According to Tunes et al (2008), monocarboxylic acids, such as acetic acid, alter the composition of organic acids in the plasma membrane, promoting a reduction in the proportion of polyunsaturated acids, and affecting important properties of the membrane, such as selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…According to the data from Tunes et al (2008), who studied the concentrations of acetic, propionic and butyric acids in the oat cultivars URS 23 and UPF 16, with increasing concentrations of organic acids, there is a reduction in both the length and the weight of dry matter of roots, and it was concluded that these acids affect the physiological quality of oat seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Na dose de 16mM, houve redução de 37% na germinação, quando comparada à dose de 0mM. Resultados semelhantes foram obtidos por TUNES et al (2008) em sementes de em cevada, trigo e aveia. No entanto, os ácidos acético e propiônico não infl uenciaram nos resultados da primeira contagem da germinação (Figura 1B), que é considerado um teste de vigor, o qual, segundo NEVES et al (2007), é indispensável para avaliar os efeitos desses ácidos nas sementes, juntamente com testes de germinação e de viabilidade.…”
Section: Resultsunclassified